PENGARUH PENGETAHUAN TERHADAP MINAT INVESTASI PASAR MODAL SYARIAH SIVITAS AKADEMIKA STIU AL-HIKMAH JAKARTA - M. Sofwan Jauhari; Abdul Ghoni (Ad-Deenar: Jurnal Ekonomi dan Bisnis Islam, 2022)
Indonesia is the largest Muslim country in the world. However, the development of Islamic financial institutions such as capital markets based on Islamic values is not as expected. Indonesia has not been able to play a big role to be the center of Islamic financial transactions. Malaysia as a country that is much smaller than Indonesia has a strategic role in the development of Islamic finance at the international level. This study wants to examine whether knowledge and understanding of the Islamic capital market is one of the factors that have a significant effect on investment interest in the Islamic capital market. This study used mixed methods that combines qualitative and quantitative approaches by making the academic community of STIU Dirosat Islamiyah Al-Hikmah as respondents. The results of this study prove that understanding and knowledge of Islamic capital market has a significant influence up to 29.5% on interest in investing in the Islamic capital market. So, it can be concluded that the level of understanding and knowledge of a Muslim towards Islamic capital market is directly proportional to his interest in investing. The higher the knowledge possessed, the higher the level of investment interest, conversely the lower level of Muslim’s knowledge, the lower investment interest he has.